Blood Gas Analysis as A Predictor of Mortality in Critical COVID-19 Patients in Dr. Moewardi Hospital Surakarta - Maria Sekar Cahyaningrum; Dian Ariningrum; Widana Primaningtyas; Tonang Dwi Ardyanto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
COVID-19 has been declared a global pandemic affecting many countries, including Indonesia. The worsening of COVID-19 patients may go unnoticed because one of the clinical manifestations of COVID-19 is silent hypoxia, where the patients’ blood oxygen saturation drops with no visible symptoms. Blood gas analysis is needed to detect silent hypoxia. This study aims to confirm whether blood gas analysis results correlate with the mortality of critical COVID-19 patients. This was a retrospective cohort study, the samples were taken from the medical records of critical COVID-19 patients from May 2020-July 2021. The variables observed were gender, age, comorbidities, oxygen saturation (SaO2), partial pressure of oxygen (PaO2), partial pressure of carbon dioxide (PaCO2), bicarbonate (HCO3-), and blood pH. Descriptive statistics, bivariate, and multivariate analyses were done. There were 210 samples, where 137 patients survived (65.24%) and 73 patients died (34.76%). The data analysis showed that comorbidities and blood pH significantly correlate with the mortality of critical COVID-19 patients, with p-values < 0.05; indicating that comorbidities and blood pH can be used as mortality predictors in critical COVID-19 patients. The RR for comorbidities and blood pH were 2.194 and 2>294, respectively, with CI 95% 1.202-4.833 for comorbidities and 1.151-5.295 for blood pH. The cut-off value used for blood pH was 7.310.